Weather anomaly monitoring method based on sensor network technology - Rahozin, D.V. (Інститут програмних систем НАН України, 2017)
In the paper a method for meteorological forecast precision improvement was proposed, the method is based on analogy search in a weather measurement history, which was received from the wireless sensor network and weather forecast history data. A methodic is proposed for obtaining warnings for possible local dangerous weather conditions also based on analogy search in the weather measurements history. Results of weather data processing and weather anomaly search are demonstrated and analyzed.